PENINGKATAN SOSIAL EKONOMI MELALUI PROGRAM DESA WISATA (STUDI DI KAMPUNG TOGA PAMEKASAN) - Jailani, Abd. Qadir (Al-Amien Prenduan for Islamic Institute, 2023)
The tradition of using medicinal plants in the form of traditional herbs among the community has been carried out for generations, because each herb made from plant raw materials is believed to have certain properties. The existence of a toga village as a tourist village that can provide education for the community to promote healthy living traditionally, but there are rapid cultural and technological changes that provide challenges related to the preservation of traditional culture. This research focuses on analyzing how to preserve the tourism village program in the village of family medicinal plants (TOGA), as well as its socio-economic impact on the community in the toga village. This research uses qualitative methods with the type of field research, the data sources used come from primary and secondary data, data collection procedures are carried out by interview, document analysis and observation. Data analysis was carried out in three stages, starting from reducing data, presenting data and drawing data conclusions. The results of this study explain how to preserve the tourist village program in the village of family medicinal plants (TOGA) through the back to nature program, recovery of tourist villages and the provision of furniture. As for the socio-economic impact on the community, the toga village has an impact on increasing community income through sales transactions of superior healthy products of the toga village. Sales of Toga Village's superior products are carried out through direct distribution to visitors and indirect distribution through shops and stalls in Toga Village.